2005
DOI: 10.1517/14712598.5.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Antisense approaches for inhibiting respiratory syncytial virus

Abstract: Respiratory syncytial virus (RSV) continues as an emerging infectious disease not only among infants and children, but also for the immune-suppressed, hospitalised and the elderly. To date, ribavirin (Virazole, ICN Pharmaceuticals, Inc.) remains the only therapeutic agent approved for the treatment of RSV. However, its clinical benefits are small and occur only in a fraction of RSV-infected patients. The prophylactic administration of palivizumab (Synagis, MedImmune, Inc.) is problematic and costly and, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…While a large number of anti-RSV therapeutic strategies have been evaluated, including strategies that use antisense oligonucleotides (12,52,71), deoxyribozymes (79,83,84), small-molecule inhibitors (15,16,55), fusion protein inhibitors (22,26,56), and morpholino compounds (42), no approach has led to any new positive clinical data or FDA-approved products. At the same time, the level of unmet need for safe and effective therapies remains high because of the more than 125,000 pediatric hospitalizations (61) and 170,000 adult hospitalizations (19) in the United States annually.…”
Section: Discussionmentioning
confidence: 99%
“…While a large number of anti-RSV therapeutic strategies have been evaluated, including strategies that use antisense oligonucleotides (12,52,71), deoxyribozymes (79,83,84), small-molecule inhibitors (15,16,55), fusion protein inhibitors (22,26,56), and morpholino compounds (42), no approach has led to any new positive clinical data or FDA-approved products. At the same time, the level of unmet need for safe and effective therapies remains high because of the more than 125,000 pediatric hospitalizations (61) and 170,000 adult hospitalizations (19) in the United States annually.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only siRNAs have advanced to clinical trials and will be discussed herein. For a thorough review of antisense approaches targeting RSV, see reference[48]. …”
Section: Drug Candidates Targeting Rsvmentioning
confidence: 99%
“…Introduction drug, Vitravene, for the treatment of cytomegalovirus (CMV) that caused retinitis in 1998 [13], a large number of antisense compounds have been studied using in vitro and in vivo models and several have been evaluated in human clinical trials [14,15]. For antiviral therapy, many published studies have shown that ASOs can inhibit various viral pathogens such as human immunodeficiency virus (HIV) [16,17], Epstein-Barr virus (EBV) [18], hepatitis B virus (HBV) [19], hepatitis C virus (HCV) [20], respiratory syncytial virus [21,22], and influenza virus [23][24][25] by interactions with essential viral genes [26]. However, ASOs specific for the 5′-terminal conserved sequences of all eight influenza A viral RNAs have not been demonstrated so far.…”
mentioning
confidence: 99%